PENGARUH MOTIVASI KERJA, KECERDASAN EMOSIONAL DAN KOMITMEN INDIVIDU TERHADAP KINERJA PERSONEL SUBDEN 3 DEN A PELOPOR SATUAN BRIMOB POLDA JATIM DI PAMEKASAN - jurnalmap map; Safril Selfianto; Indra Prasetyo; Chamariyah ÔÇÄ (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
This research was conducted in Subden 3 Den A Pioneer Unit Brimob East Java Police in Pamekasan with the number of research samples as many as 118 people. The purpose of this study is 1) to describe how about work motivation, emotional intelligence, individual commitment and performance of personnel, 2) to find out whether the work motivation, emotional intelligence and individual commitment affect simultaneously to the performance of personnel, 3) to find out whether the work motivation, emotional intelligence and individual commitment partially influence the performance of personnel. The results showed that simultaneously, Work Motivation, Emotional Intelligence and Individual Commitment have a significant influence on the performance of personnel. Partially, Work Motivation, Emotional Intelligence and Individual Commitment have a significant influence on Personnel Performance.Keywords: work motivation, emotional intelligence, individual commitment, personnel performance